Neoartic valve insufficiency assessment after pulmonary autograft implantation in pediatric patients during long term follow-up - Romanyuk, O. N.; Klymyshyn, Y. I.; Artemenko, E. A.; Dzyurman, D. O.; Rudenko, N. N. (Ukrainian Journal of Cardiovascular Surgery, 2017)
An alternative method of aortic valve surgical treatment in children of different age groups is pulmonary au-tograft implantation. After detailed study of operational results we identified predictors of neoaortic valve insufficiency and neoaortic root dilatation in a remote postoperative period. Purpose: tо analyze autograft dysfunction causes in postoperative period and to evaluate the influence of root reinforce-ment techniques on neoaortic valve insufficiency and neoaortic root dilatation development in long term period. Materials and methods. 151 consecutive patients <18 years age group, which undergone pulmonary autograft implanta-tion in period between 1996 and 2014. Results. Neoaortic root enlargement over age norms during 15-year observation period occurred at all three levels. Basal ring diameter (BR) changed from 1,32±1,1 (-2; 5,3) units in the early postoperative period to 3,2±1,3 (0,3; 5,4) in a remote period, sinuses Valsalva (SV) - from 1,63±1,2 (-1,6; 4,4) to 4,2±1,7 (0,5; 8,8), sinotubular junction (STJ) – from 1,8±1,1 (-1; 5,6) to 4,6±2,2 (0,8; 10,6) (p=0.001). BR dilatation in the remote period was observed in 46,3% (n=70) patients, SV dilation – in 67,7% (n=23) and STJ – in 58,8% (n=89) of patients. Conclusions. Neoaortic root dilatation and neoaortic valve insufficiency development is the most common cause of autograft dysfunction and is typical for the late period in patients after pulmonary autograft implantation. Application of autograft root reinforcement concept strengthening at two levels significantly reduced the degree of neoartic root dilatation and neoaortic valve insufficiency incidence in our study.